SEME (SOCIAL AND ECOLOGYCAL MARKET ECONOMY) TERHADAP KEBERLANJUTAN SUMBERDAYA PERIKANAN DAN KESEJAHTERAAN NELAYAN - Ivonne Raystika Gretha Kaya; Sajriawati Sajriawati (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Fisheries resources are very vulnerable. Integrated management is needed between regions, sectors and stakeholders to sustain fisheries resources. Good management will provide the maximum benefits of the environment, economy and society. "Social and Ecological Market Economy" (SEME) is based on determining a triangle strategic, is the combination of capital, labor and environmental sustainability. This concept is needed as a benchmark in maintaining a balance between resource sustainability, fishermen as beneficiaries and the economic side to ensure the sustainability of fishermen's lives and prevent poverty. Some of the instruments that can be implemented based on the SEME concept are: 1) Supporting laws and regulations, 2) Improving the local market economy, 3) Creating a network of cooperation, and 4) Forming fishing activities and businesses based on environmental sustainability.